2019
DOI: 10.1002/wmh3.295
|View full text |Cite
|
Sign up to set email alerts
|

Access to Essential Medications and Equipment for Obstetric and Neonatal Primary Care in Bombali District, Sierra Leone

Abstract: The increased demand for basic emergency obstetric and neonatal care (BEmONC) services in Sierra Leone since the launch of the nationwide free maternity care initiative in 2010 has strained the capacity of the system to provide high‐quality care. In 2014, members of our research team visited all 97 functioning primary health‐care facilities in Bombali district in the Northern Province of Sierra Leone to evaluate gaps in access to BEmONC. Although most facilities had the equipment necessary for maternal and neo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The barriers related to the relationship with norms and standards for the EDL implementation included poor availability of diagnosis and management guidelines, noting the unavailability of diabetes guidelines in any surveyed clinics 165 . Other barriers unique to the EML included incompliance to guidelines 50,53,131,149,153,166,168,169 , incompliance to national EMLs 48,68,79,132,145,170 , lack of national EMLs in facilities 128,171 , disconnect between guidelines on treatment protocols 47,75 , disconnect between policy, guidelines and practice 46,167 , and lack of standard operating procedures 135 .…”
Section: Relationship With Norms and Standardsmentioning
confidence: 99%
See 1 more Smart Citation
“…The barriers related to the relationship with norms and standards for the EDL implementation included poor availability of diagnosis and management guidelines, noting the unavailability of diabetes guidelines in any surveyed clinics 165 . Other barriers unique to the EML included incompliance to guidelines 50,53,131,149,153,166,168,169 , incompliance to national EMLs 48,68,79,132,145,170 , lack of national EMLs in facilities 128,171 , disconnect between guidelines on treatment protocols 47,75 , disconnect between policy, guidelines and practice 46,167 , and lack of standard operating procedures 135 .…”
Section: Relationship With Norms and Standardsmentioning
confidence: 99%
“…Unavailability of guidelines was the most prominent theme within the barriers related to relationship with norms and standards for the EML implementation 35,66,86,106,110,116,154,166,143,59,106,119,131,143,155,167 . Other barriers unique to the EML included incompliance to guidelines 50,53,131,149,153,166,168,169 , incompliance to national EMLs 48,68,79,132,145,170 , lack of national EMLs in facilities 128,171 , disconnect between guidelines on treatment protocols 47,75 , disconnect between policy, guidelines and practice 46,167 , and lack of standard operating procedures 135 .…”
Section: Relationship With Norms and Standardsmentioning
confidence: 99%
“…Facility midwifery care services need to improve by providing equipment and supplies to increase satisfaction with services received during the intrapartum stage of pregnant women [9]. A study in Sierra Leone indicated that the checklist entries for labour regarding delivery equipment could improve optimum care during intrapartum monitoring and delivery for pregnant women [10]. Significantly, the maintenance of equipment should be prioritised to achieve optimum monitoring and delivery for a pregnant woman effectively [10].…”
Section: Introductionmentioning
confidence: 99%
“…A study in Sierra Leone indicated that the checklist entries for labour regarding delivery equipment could improve optimum care during intrapartum monitoring and delivery for pregnant women [10]. Significantly, the maintenance of equipment should be prioritised to achieve optimum monitoring and delivery for a pregnant woman effectively [10]. High-quality care is needed during labour.…”
Section: Introductionmentioning
confidence: 99%